Effects of a museum-based social prescription intervention on quantitative measures of psychological wellbeing in older adults. (January 2018) - Thomson, Linda J; Lockyer, Bridget; Camic, Paul M; Chatterjee, Helen J
Aims: To assess psychological wellbeing in a novel social prescription intervention for older adults called Museums on Prescription and to explore the extent of change over time in six self-rated emotions ('absorbed', 'active', 'cheerful', 'encouraged', 'enlightened' and 'inspired'). Methods: Participants ( n = 115) aged 65–94 years were referred to museum-based programmes comprising 10 weekly sessions, by healthcare and third sector organisations using inclusion criteria (e.g. socially isolated, able to give informed consent, not in employment, not regularly attending social or cultural activities) and exclusion criteria (e.g. unable to travel to the museum, unable to function in a group situation, unlikely to be able to attend all sessions, unable to take part in interviews and complete questionnaires). In a within-participants' design, the Museum Wellbeing Measure for Older Adults (MWM-OA) was administered pre-post session at start-, mid- and end-programme. A total of 12 programmes, facilitated by museum staff and volunteers, were conducted in seven museums in central London and across Kent. In addition to the quantitative measures, participants, carers where present, museum staff and researchers kept weekly diaries following guideline questions and took part in end-programme in-depth interviews. Results: Multivariate analyses of variance showed significant participant improvements in all six MWM-OA emotions, pre-post session at start-, mid- and end-programme. Two emotions, 'absorbed' and 'enlightened', increased pre-post session disproportionately to the others; 'cheerful' attained the highest pre-post session scores whereas 'active' was consistently lowest. Conclusion: Museums can be instrumental in offering museum-based programmes for older adults to improve psychological wellbeing over time. Participants in the study experienced a sense of privilege, valued the opportunity to liaise with curators, visit parts of the museum closed to the public and handle objects normally behind glass. Participants appreciated opportunities afforded by creative and co-productive activities to acquire learning and skills, and get to know new people in a different context.